The effect of different oral hygiene regimes on thin gingival biotype - Mohd Hamzah, Mariah; Md Yusoff, Su’aidah Aisyah; Said, Ummi Nabilah; Kamil, Wisam Alaa (2015)
Objectives: To determine if different plaque control measures have any effect on thin gingival biotype. Materials and Methods: Twenty systemically healthy females, of thin gingival biotype and with mild to moderate gingivitis, were recruited for the study. Subjects were randomized consecutively to one of two groups: the test group (TG, n=10) or the control group (CG, n=10). Clinical periodontal parameters, including percentages of sites with the presence of plaque scores (%PS), bleeding on probing (%BOP) and probing pocket depth (PPD), were recorded at baseline. All subjects received nonsurgical periodontal therapy, which included oral hygiene instructions (OHI) and supra/subgingival scaling and prophylaxis. Participants in TG received a localized single episode of photodynamic therapy (PDT) at incisor teeth. The OHI given to TG comprised the use of toothpaste with manual toothbrush, dental floss and mouthrinse, whereby the OHI to CG were restricted to manual tooth brushing using toothpaste only. The periodontal scores were recorded at 1 and 2 months re-evaluation (RE) after periodontal therapy. Results: The periodontal treatment with oral hygiene regimes in both groups resulted in a significant decrease in mean %BOP at 2 months re-evaluation (p<0.05). The mean %PS and %BOP of the incisors in the TG significantly decreased at 1st and 2nd RE (p<0.05), while these periodontal records in CG showed significant reductions only at 2 months after treatment. Conclusion: This study demonstrated that specific plaque control approaches might result in a significant reduction in periodontal inflammation in thin gingival biotype patients.